2014
DOI: 10.7860/jcdr/2014/9892.4860
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Histometrical Evaluation of two Synthetic Hydroxyapatite Based Biomaterials in the Experimental Periodontal Defects in Dogs

Abstract: Histological study showed similar healing pattern with both the types of bone graft materials with maturing bone at 3 months and advanced osteogenesis at six months in experimental intraosseous periodontal defects in dogs. However, histological evaluation for longer period is necessary to determine the time taken for complete replacement of the bone graft materials with new bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We further adopted histological observations and histomorphometric analysis ( Figure 8 ) to assess the newly formed bone tissue. 65 DBBM are deproteinized, decellularized and sintered bovine cancellous bone chips and its major component is hydroxyapatite. 66 Due to its excellent biocompatibility and osteconductivity, DBBM is one of the most frequently used materials in GBR technique.…”
Section: Resultsmentioning
confidence: 99%
“…We further adopted histological observations and histomorphometric analysis ( Figure 8 ) to assess the newly formed bone tissue. 65 DBBM are deproteinized, decellularized and sintered bovine cancellous bone chips and its major component is hydroxyapatite. 66 Due to its excellent biocompatibility and osteconductivity, DBBM is one of the most frequently used materials in GBR technique.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the collagen sponge consisted of bio-suitable atelocollagen and is widely applied as artificial skin [ 37 , 38 ]. Low degradable biomaterial remains in periodontal tissue long-term after surgery, increasing the risk of infection or prevention of repair [ 39 ]. Histological specimens showed that collagen implants were mostly degraded at 4 weeks post-surgery.…”
Section: Discussionmentioning
confidence: 99%